Effect of a single dose of lidocaine and ketamine on intraoperative opioids requirements in patients undergoing elective gynecological laparotomies under general anesthesia. A randomized, placebo controlled pilot study - Jusset Teresa García-Navia; Javier Tornero López; Juan José Egea-Guerrero; Angel Vilches Arenas; Tiburcio Vázquez Gutiérrez (Farmacia Hospitalaria, 2016)
Background and goal of study: there is evidence that perioperative intravenous ketamine and lidocaine reduce postoperative pain, postoperative opioids consumption, shortens hospital stay and accelerates intestinal function recovery. However, it has not been studied the beneficial effects in the intraoperative period. The aim of this study was to evaluate the effect of a single dose of lidocaine and ketamine on intraoperative opioids requirements in patients undergoing elective gynecological laparotomies under general anesthesia. Materials and methods: we performed a single-centre, prospective, randomized, double-blinded, placebo-controlled study. We included 33 patients (11 in the ketamine group, 11 in the lidocaine group and 11 in the placebo group). Postoperative analgesia was accomplished by patient-controlled morphine. Patients were randomly assigned to receive either a 1.5 mg/kg of 2% lidocaine, 0.5 mg/kg of 5% ketamine or 0.9% saline bolus. The primary outcome was the opioids consumption during surgery. The secondary outcomes included: emergence time, pain scores, opioids consumption within 24 h after surgery and side effects. Results: decreased intraoperative opioids requirements were noted in the experimental groups (ketamine: 402.3 } 106.3 and lidocaine: 397.7 } 107.5, compared with saline: 561.4 } 97.1); p = 0.001. We found a positive correlation between intraoperative opioids consumption and emergence time (r = 0.864, p < 0.001). There was no significant difference between the groups in VAS pain scores at rest within the first 24 postoperative hours. Total morphine consumption within 24 h after surgery did not differ significantly among the groups (placebo: 27.54 } 11.75; ketamine: 30.95 } 7.88; lidocaine 34.77 } 10.25; p = 0.26). Postoperative nausea and vomiting were more common in placebo group (it was observed in 3 subjects in ketamine group, in 5 subjects in lidocaine group and in 9 subjects in placebo group; p = 0.027). Conclusion: our results do not support the use of intraoperative single dose of lidocaine or ketamine to reduce postoperative pain and postoperative opioids consumption after open gynecological surgery. However, they seem to decrease intraoperative opioids requirements and shorten emergence time. Nevertheless, these findings should be validating in further studies with large sample size.